Immediately sequential bilateral cataract surgery in Down syndrome - Rishi Sharma; Sandeep Shankar; Nitesh Kumar; Nitin Vichhare (Indian Journal of Ophthalmology, 2022)
The exponential increase in world population and average human lifespan is expected to result in geriatric population globally. The problem of preventable blindness due to cataract will increase manifold. Simultaneous Bilateral cataract surgery (SBCS) is a viable option in such subset of patients. Despite faster visual recovery, economic benefits to patients and health care providers, decreased risk of complications associated with General anaesthesia, there is significant resistance in accepting SBCS as a routine procedure. Bilateral endophthalmitis is the main deterrent in performing ISBCS. This case highlights successful ISBCS in 36 years old female patient with Down's syndrome.